KEBIJAKAN PENOLAKAN RUSIA TERHADAP STRATEGI BARAT DI SURIAH - Irdayanti Irdayanti (An-Nida', 2012)
This paper attempts to explain the reasons for rejection of Russia against the West in solving conflict in Syria. This paper uses a descriptive approach to analysis of Russia’s policy in Syria. Syria is one of the countries in Middle East that is experiencing political turmoil with people demanding President Bashar al-Assad retreated from his position. This conflict has claimed of so many people life that western countries lead to implement the arms and other economic sanctions against Syria but the effort was opposed by Russia through its veto. The balance of power theory tries to explain the refusal of Russia as a form of maintaining power in Middle East, particularly Syria. Russians view the necessary dialogue between the government and the opposition to resolve conflicts rather than international condemnation of Syria.